Hubungan Status Ekonomi Dan Paritas Dengan Pemilihan Alat Kontrasepsi Hormonal - Elna Susiana; Ika Friscila; Nurul Hidayah; Novita Dewi Iswandari (STIKES Bina Usada Bali, 2026)
Background: The use of hormonal contraceptives such as injections and pills continues to dominate the choices of active family planning (FP) acceptors in the working area of Puskesmas Makunjung, while long-term methods such as intrauterine devices (IUDs) remain very low. This preference is suspected to be influenced by the economic status and parity of the acceptors. Methodology: This study employed a quantitative approach with a cross-sectional design. The sample consisted of 33 active FP acceptors selected through accidental sampling. Data analysis was conducted using the Fisher Exact test to examine the relationship between economic status and parity with the choice of hormonal contraceptive methods. Result: The most common hormonal contraceptive choice was injections (54.5%), followed by pills (24.2%), and implants (21.2%). Most respondents came from the low economic group (66.7%) and had non-risk parity (2–3 children) at 77.8%. The analysis showed a significant relationship between economic status and the choice of hormonal contraceptive methods (p = 0.024), while no significant relationship was found between parity and contraceptive choice (p = 0.739). Conclusions: There is a relationship between economic status and the choice of hormonal contraceptives in the working area of Puskesmas Makunjung; however, no relationship was found between parity and contraceptive choice in the same area. It is recommended that Puskesmas Makunjung be more proactive in providing education and counseling on long-term contraceptive methods, particularly for acceptors from low-income groups.